Penerapan Manajemen Risiko Berbasis ISO 31000 Pada Depot Air Minum Isi Ulang Amanda Cibangkong Kota Bandung - Nira Destiani Dewi; Chika Putri Irwanda; Nabila Zulfa Azizah; Nurul Laily Oktaviana; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study analyzes the implementation of risk management based on ISO 31000 in the Amanda Refill Water Depot, a small and medium enterprise (SME) located in Cibangkong, Bandung City. The purpose of this study is to identify potential risks, assess their likelihood and impact, and evaluate mitigation efforts in accordance with ISO 31000. The research method used is a descriptive qualitative approach through interviews and direct observation. The findings indicate that the main risks encountered include occasional machine damage, power outages, and leaking gallons, although these occur infrequently. The business’s strength lies in consistent cleanliness and customer trust, while weaknesses are found in the absence of online promotion and delivery services. A notable threat is the lack of a digital presence on Google Maps, which may reduce market visibility. The study concludes that while the depot informally applies risk management principles in daily operations, improvements are still needed in formal documentation, standard operating procedures, and digital adaptation to strengthen resilience and competitiveness.